Ethnogeriatrics : Healthcare Needs of Diverse Populations - Cummings-Vaughn, Lenise; Cruz-Oliver, Dulce M. (Springer International Publishing : Imprint: Springer, 2017)
This title is divided into five parts that discuss ethnogeriatric foundations, research issues, clinical care in ethnogeriatrics, education and policy. Expertly written chapters present a systematic approach to recognizing, analyzing and addressing the challenges of meeting the healthcare needs of a diverse population and authors discuss ways in which to engage the community by increasing research participation and by investigating the most prevalent diseases found in ethnic minorities. Ethnogeriatrics: Healthcare Needs of Diverse Populations discusses issues related to working with culturally diverse elders that tend not to be addressed in typical training curricula and is essential reading for geriatricians, hospitalists, advance practice nurses, social workers and all others who provide high quality care to older patients.- Resumé vydavatel